Effect of filling technique and light-curing exposure time on the hardness of bulk-fill resin composites - Besegato, João Felipe; Petrin, Débora de Castro Costa; Costa, Giovana Cazarim da; Ferraresso, Lucas Fernando de Oliveira Tomaz; Hoeppner, Márcio Grama (Clinical and Laboratorial Research in Dentistry, 2020)
Objectives: This study evaluated the effect of filling techniques and light-curing time on Vickers hardness of bulk fill composite resins (BFCR). Methods: BFCR high viscosity Opus Bulk Fill (OBF) and low viscosity Opus Bulk Fill Flow (OBFF), were placed in cylindrical samples of poly methyl methacrylate with height and internal diameter of 4 mm, and randomly assigned into six groups (G) according to the filling technique (I1-single increment of 4 mm thickness and I2 – increment of 2 mm thickness) and light-curing time of each increment with an irradiance of 1000 mW/cm2 (T1 – 20 seconds and T2 – 40 seconds): G1 – OBFI1T1, G2 – OBFI2T1, G3 – OBFI1T2, G4 – OBFI2T2, G5 – OBFF+OBFI2T1 e G6 – OBFF+OBFI2T2. Hardness was measured in the top and bottom surface of each sample. Twoway ANOVA followed by Tukey’s post-test were used for analysis with a significance level of 5%. Results: There was no difference in hardness on the top surface, regardless of the filling technique and light-curing exposure time used. However, in the bottom surface differences were observed regarding the filling technique and light-curing time, except between the G3 and G4 groups. All samples showed significant hardness reduction at the bottom compared to the top surface. Conclusions: The lowest light-curing time (20 seconds) must be considered with caution, as it resulted in the reduction of hardness in the area farther from the light source. The OBFF exhibited lower hardness than OBF, despite of the light-curing exposure time.